2012
DOI: 10.1145/2347736.2347748
|View full text |Cite
|
Sign up to set email alerts
|

Computing as if infrastructure mattered

Abstract: Understanding the technical and social fundamentals of the computing infrastructure is essential in the continuously evolving technological realm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…It has been suggested that such mechanisms should be integrated into IoT middleware to perform data analysis operations on data streams. ''Computational thinking'' (Wing, 2006) calls for increased attention to building computing infrastructures that are mindful of the real-world complexities and engage with the existing economic and social aspects (Blanchette, 2012). This gap could be addressed by processing streams efficiently, by handling different formats and models as well as energy limitations of IoT environments (Mineraud et al, 2016), and by the timely generation of real-time information for IoT applications (Díaz et al, 2016).…”
Section: Designing Architectures For Iotmentioning
confidence: 99%
“…It has been suggested that such mechanisms should be integrated into IoT middleware to perform data analysis operations on data streams. ''Computational thinking'' (Wing, 2006) calls for increased attention to building computing infrastructures that are mindful of the real-world complexities and engage with the existing economic and social aspects (Blanchette, 2012). This gap could be addressed by processing streams efficiently, by handling different formats and models as well as energy limitations of IoT environments (Mineraud et al, 2016), and by the timely generation of real-time information for IoT applications (Díaz et al, 2016).…”
Section: Designing Architectures For Iotmentioning
confidence: 99%
“…One output from the desk research literature review was the production of core and secondary readings. The decision was made that all current and new team members should at a minimum familiarise themselves with the core readings by Ali [7,8], Blanchette [9], Dennis [10] and Malazita and Resetar [11].…”
Section: Documenting the Project Scopementioning
confidence: 99%
“…This perspective recognizes that automated actions and decisions are shaped by the intricate interplay between algorithms and the technical elements and subsystems they are networked with (e.g., sensorimotor subsystems). At the same time, they depend on contextual factors, arising through reciprocal interactions with the infrastructure of the built environment and the physical world of objects and people (Kitchin and Dodge 2011 , see also Blanchette 2012 ). Drawing on the state-of-the-art in driving research, the article then delves into some of the key challenges currently hindering the introduction of SDCs into cities.…”
Section: Introductionmentioning
confidence: 99%